2022
DOI: 10.1101/2022.07.11.22277435
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systems-level patterns in biological processes are changed under prolongevity interventions and across biological age

Abstract: Aging manifests as progressive deterioration in cellular and systemic homeostasis, requiring systems-level perspectives to understand the gradual molecular dysregulation of underlying biological processes. Here, we report systems-level changes in the molecular regulation of biological processes under multiple lifespan-extending interventions in mice and across age in humans. In mouse cohorts, Differential Rank Conservation (DIRAC) analyses of liver proteomics and transcriptomics show that mechanistically disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that 17α-estradiol extends the lifespan of male mice, has beneficial effects on metabolism and inflammation with a similar mechanism as that of rapamycin and acarbose [6][7][8]. Further investigations revealed certain unique features of 17α-estradiol in life extension distinct to rapamycin and acarbose [9,10]. Further, 17α-estradiol was shown to target hypothalamic POMC neurons to reduce metabolism by decreasing feeding behavior via anorexigenic pathways [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that 17α-estradiol extends the lifespan of male mice, has beneficial effects on metabolism and inflammation with a similar mechanism as that of rapamycin and acarbose [6][7][8]. Further investigations revealed certain unique features of 17α-estradiol in life extension distinct to rapamycin and acarbose [9,10]. Further, 17α-estradiol was shown to target hypothalamic POMC neurons to reduce metabolism by decreasing feeding behavior via anorexigenic pathways [11].…”
Section: Introductionmentioning
confidence: 99%